Treatment of simple bone cysts using endoscopic curettage: a case series analysis - Hisaki Aiba; Masaaki Kobayashi; Yuko Waguri-Nagaya; Hideyuki Goto; Jun Mizutani; Satoshi Yamada; Hideki Okamoto; Masahiro Nozaki; Hiroto Mitsui; Shinji Miwa; Makoto Kobayashi; Kojiro Endo; et al. (Journal of Orthopaedic Surgery and Research, 2018)
Abstract Background Endoscopic curettage is considered applicable for the treatment of simple bone cysts with the expectation that it might be less invasive than open curettage. In this study, we investigated the efficacy of endoscopic curettage for the treatment of simple bone cysts. The goal was to investigate the incidence of cyst recurrence and bone healing after endoscopic curettage. Moreover, complications and functionality at the final follow-up were evaluated. Methods From 2003 to 2014, 37 patients with simple bone cysts underwent endoscopic curettage. Twenty-four were male and 13 were female, with a mean age of 14.7 years. Endoscopic curettage was performed with the support of an arthroscope via 7–8 mm holes penetrated by cannulated drills with a small incision. The cysts underwent curettage using angled curettes, rongeurs, and an electrical shaver until the normal bone was observed in the medullary cavity. To investigate the bone healing after endoscopic curettage, we evaluated the consolidation of the cyst at the final evaluation (Modified Neer Classification) and the time to solid union after operation, which was defined as the sufficient thickness of the cortical bone to prevent fracture and allow physical activities. Results Recurrence occurred in seven patients (18.9%). A log-rank analysis revealed that contact with the physis was associated with recurrence (p = 0.006). Among 31 patients (83.7%), the consolidation of cyst was considered healed at the final X-ray follow-up period, and in these patients, the mean time taken for solid union of cortical bone thinning was 4.0 months (standard deviation, 2.4). With regard to major complications of endoscopic curettage, a transient radial nerve palsy and two postoperative fractures occurred. The former problem was managed conservatively and the latter problems by transient internal fixation; these problems were managed without any further complications. All patients had a good postoperative function. Conclusions Endoscopic curettage might be a useful alternative as it is a minimally invasive procedure for the treatment of simple bone cysts. Considering the relatively smaller size of this study, further investigation should be necessary for deducing the reliable conclusion.